Implementation of Anti-Corruption Values ​​in Pancasila Education Learning - Aprillya Sulistyo, Vania; Sabrina Zuriya Ramadhani, Sabrina; Indah Permata Sari, Indah; Rahmaddanni, Rahmaddanni; Razani , Abiyyu; Lukman, Asra; Febriani Nduru (Borneo Novelty Publishing, 2024)
This study aims to analyze the implementation of anti-corruption values in Pancasila's learning in high schools. Anti-corruption education is an important aspect in forming a young generation with integrity, and Pancasila as the foundation of the Indonesian state provides a strong ethical framework for teaching the values ​​of honesty, justice, and responsibility. Using qualitative methods through literature studies, this study analyses various academic sources and policies related to character education and anti-corruption. The results of the study indicate that, although many schools have attempted to integrate anti-corruption values into the Pancasila curriculum, its implementation still faces challenges such as limited teaching time, varying teacher understanding, and a lack of specific teaching materials. Students generally understand the importance of anti-corruption values, but their application in everyday life is still weak due to the influence of the social environment. This study recommends strengthening teacher training, providing relevant teaching materials, and better policy support from schools to improve the effectiveness of anti-corruption education. Thus, Pancasila education can contribute more significantly to forming a young generation with integrity and free from corrupt practices.